E-learning in teacher training - Kokovay, Ágnes; Kakuk, Andrea (Teaching Mathematics and Computer Science, 2006)
A research has been organised with three Colleges taking part during the academic year of 2002-03. These institutions were• The Teacher's Training College of Baja• Eszerházy Károly College of Eger• The College of NyíregyházaThe aim of the research was to reveal differences between results of students studying in the traditional way and of students using e-learning.The survey has been carried out among students of PE (physical education). A distance educational programme (Basics of Gymnastics) developoed before launching the survey served as basis for the survey [5]. The results of the research were first presented at the Agria-Média Conference in 2004. After analysing the results the findings were presented at the 3rd International Conference on Education and Information Systems in Orlando, Florida in July 2005.This paper tries to reveal the structure of the e-learning programme, the environment of the research and the latest results found after the final analyses of the research.